2016
DOI: 10.1099/jmm.0.000255
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of clinical and environmental triazole-resistant Aspergillus fumigatus in Iran: is it a challenging issue?

Abstract: Triazole antifungal agents are the mainstay of aspergillosis treatment. As highlighted in numerous studies, the global increase in the prevalence of triazole resistance could hamper the management of aspergillosis. In the present three-year study, 513 samples (213 clinical and 300 environmental samples) from 10 provinces of Iran were processed and screened in terms of azole resistance (4 and 1 mg l À1 of itraconazole and voriconazole, respectively), using selective plates. Overall, 150 A. fumigatus isolates (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 48 publications
3
53
0
Order By: Relevance
“…New generation of azoles and echinocandins might be useful in this regard. However, based on a recent report from Iran, the number of azole-resistant A. fumigatus strains against itraconazole increased significantly from 3% to 6% [16]. Some studies indicated that mutations might confer resistance to individual azoles, rather than to the whole class [17].…”
Section: Discussionmentioning
confidence: 99%
“…New generation of azoles and echinocandins might be useful in this regard. However, based on a recent report from Iran, the number of azole-resistant A. fumigatus strains against itraconazole increased significantly from 3% to 6% [16]. Some studies indicated that mutations might confer resistance to individual azoles, rather than to the whole class [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 29 environmental isolates were collected from soil and leaves of gardens surrounding hospitals and from indoor air of hospital wards. The isolates were identified by partial sequencing of the β‐tubulin gene . Antifungal susceptibility testing was performed according to Clinical and Laboratory Standards Institute guidelines (M38‐A2, 2008) .…”
Section: Methodsmentioning
confidence: 99%
“…The latter disorder is associated with immunocompromising conditions, that is, neutropenia, hematopoietic stem cell transplantation (HSCT), solid organ transplantation (SOT) and chemotherapy . Although triazole antifungal drugs (voriconazole and posaconazole) are currently the first‐line therapy in the management and prophylaxis of aspergillosis, surveillance studies and case series suggest a global presence of clinical and environmental azole‐resistant A. fumigatus isolates in Africa, Australia, Asia, Europe, Latin‐America, the Middle East and United States . Azole‐resistance may develop either in patients who are treated with long‐term azole therapy or in the environment through the exposure of the fungus to azole fungicides used in agriculture .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, molecular tests were performed for accurate identification of Aspergillus fumigatus. Briefly, DNA was extracted from the colony using homogenization by glass beads followed by phenol-chloroform purification, as described previously (5,6). Polymerase chain reaction (PCR) amplification of the β-tubulin gene was performed using the primers B2a (5'-GGTAACCAAATCGGTGCTTTC-3') and B2b ('5-ACCCTCAGTGTAGTGACCCTTGGC-3') with cycles of five minutes at 94°C for primary denaturation, followed by 35 cycles at 94°C (60 seconds), 58°C (30 seconds), and 72°C (80 seconds), with a final seven-minutes extension step at 72°C.…”
Section: Case Presentationmentioning
confidence: 99%